Students’ Motivation in Reading English Text: A Survey of Junior High School in Palembang - Depi Apriani; Manallulaili Manallulaili; Renny Kurniasari (Jadila: Journal of Development and Innovation in Language and Literature Education, 2021)
This study investigated students’ reading motivation in English text. The Quantitative research methodology carried out in this study is in order to collect information or data that is donated. Researcher used a survey with descriptive analysis that is research whose source of data and information is mainly obtained from respondents as a research sample using questionnaires as an instrument of data collection to describe students reading motivation of junior high school in Palembang. This study was conducted at SMP N 7 Pemulutan with 104 as the participants taken from the nine grade students of that school by using simple random sampling. in collecting data, the researcher used Motivation Reading Questionnaire (MRQ). The questionnaire consisted of 53 items with eleven indicators. The result covers 1. Self efficacy can make students more motivated in reading. 2. Intrinsic factor included enjoyable and students’ interest in reading. 3. Extrinsic factor covered such as for finishing assignment, for getting high getting praises, in getting high score.